Satellite DNAs are conserved and differentially transcribed among Gryllus cricket species - Palacios-Gimenez, Octavio Manuel [UNESP] (2018)
Satellite DNA (satDNA) is an abundant class of non-coding repetitive DNA that is preferentially found as tandemly repeated arrays in gene-poor heterochromatin but is also present in gene-rich euchromatin. Here, we used DNA- and RNA-seq from Gryllus assimilis to address the content and transcriptional patterns of satDNAs. We also mapped RNA-seq libraries for other Gryllus species against the satDNAs found in G. assimilis and G. bimaculatus genomes to investigate their evolutionary conservation and transcriptional profiles in Gryllus. Through DNA-seq read clustering analysis using RepeatExplorer, dotplots analysis and fluorescence in situ hybridization mapping, we found that â 1/44% of the G. assimilis genome is represented by 11 well-defined A + T-rich satDNA families. These are mainly located in heterochromatic areas, with some repeats able to form high-order repeat structures. By in silico transcriptional analysis we identified satDNAs that are conserved in Gryllus but differentially transcribed. The data regarding satDNA presence in G. assimilis genome were discussed in an evolutionary context, with transcriptional data enabling comparisons between sexes and across tissues when possible. We discuss hypotheses for the conservation and transcription of satDNAs in Gryllus, which might result from their role in sexual differentiation at the chromatin level, heterochromatin formation and centromeric function.